Bahasa Inggris - Utomo, Yudo Bismo; NurKholis, Afif; Rahayu, Putri Nur (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
This research takes the theme of the importance of interactive digital multimedia education on the impact of Tiktok social media on children. This is due to the lack of parental supervision in the use of smartphones during online learning which makes children addicted to the use of social media, especially Tiktok. Even though the pandemic has subsided and all school activities have returned offline, it seems that children are still addicted to Tiktok. If the problem is not addressed immediately, it makes children see more entertainment content on Tiktok than listening to the lessons delivered by their teachers. The purpose of this study is to create interactive digital multimedia to educate parents and children in using TikTok social media and the impact on children's health and character. Thus, parents can increase supervision of their children. The method used in this study uses the Multimedia Development Life Cycle (MDLC) method. MDLC has stages including: concept, material collection, design, implementation, and testing. The tools used in making interactive digital media in this study used Adobe Premiere and Adobe After Effect. The result of this study is that this interactive animated film can display visualizations of the impact of TikTok social media caused, both positive and negative impacts. From the effectiveness test conducted, it can be concluded that interactive digital multimedia passed the test with a percentage of 83% with a Strongly Agree (SS) scale.